Uji Aktivitas Sediaan Hand Sanitizer Ekstrak Etanol Daun Euphorbia milli Terhadap Bakteri Staphylococcus epidermidis - Sri Budiasih, Putu Eka; Sunadi Putra, I Made Agus; Santoso, Puguh (Usadha, 2024)
Euphorbia milli is a plant that has medicinal properties, one of which is that Euphorbia milli leaves contain peroxidase, saponins, calcium oxalate, peptic substances, and starch. Meanwhile, the sap contains euphorbol, euphol, and cyoartenol. The leaves are widely used as a remedy for boils (furuncle), purulent inflammation of the skin (piodermi), scalds, and burns. Euphorbia milli folia leaves contain saponins, which have potential as antibacterials. This study aims to determine the antibacterial activity of the ethanol extract of the giwang fern cactus leaves on the growth of Staphylococcus epidermidis by making a hand sanitizer gel from the giwang fern cactus leaf extract using three variations of extract concentrations: 5%, 10%, and 15%. The plant extracts were obtained using the maceration method using 70% ethanol with three replications. This research method is laboratory-experimental research. The results showed that the hand sanitizer gel had an inhibitory effect on the growth of the Staphylococcus epidermidis bacteria.